KEANEKARAGAMAN JENIS BURUNG DI HUTAN PRODUKSI DESA MALONAS KECAMATAN DAMPELAS KABUPATEN DONGGALA - Ongky, Ongky; Korja, I Nengah; Sustri, Sustri (Universitas Tadulako, 2020)
Indonesia ranks fourth in the world to the number of birds after Colombia, Peru, and Brazil. The Sulawesi island species settler bird around 224 species land and fresh water bird, which is 41 species of them were endemic types and the most endemic bird found in the Sulawesi island. The Malona’s village forest production includes the work KPH Dampelas, the forest production was of hills and mountains so that the environment has such a variety of plants that they provide food, make a nests, and shelter from any threat to this particular type of bird .The research aims to identify the diversity of birds in the forest production. The research was in forest production areas at the KPH Dampelas workplace, Malonas Village, Dampelas District, Donggala Regency on February-March 2019. observation locale in open and closed habitats, the method used was point count. Data processing by analyzing the composition of birds, diversity of kinds, attendance rates of kinds, index arrangement of kinds, kind of domination. The result was found 20 species of birds with 134 individuals, include 10 famili and 11 species built-in as endemic of birds. The value of the diversity index in forests of H '= 2.85 shows that the index of diversity of that type is moderate, the value of the index of E= 0.95 it shows the distribution of the relative uniform between species and there are 9 kinds of birds with an individual being so abundant that it becomes the dominant type of bird.Keywords: Birds, Forest Production, Biodiversity